Preliminary Study on the Development of Sigil E-Book Media in Improving Language Skills with Character Education - Anik Dwi Nurmawati; Siti Rochmiyati; Banun Banun Havifah Cahyo Khosiyono (IAIN Bengkulu, 2023)
The development of the Sigil e-book media which is used in language learning for fourth grade elementary school students is expected to increase motivation and language skills. This article will explain some of the findings of a preliminary study conducted for the development of the Sigil e-book media used in students’ language learning in fourth grade elementary school. This type of research is Research and Development (R&D). The field studies carried out included: obtaining information about the needs for developing Indonesian language learning resources. The results of this study are expected to serve as the basis for the development of Sigil e-book media used in language learning for fourth grade of elementary school to increase students' motivation and language skills. E-books are preferred over printed books on the grounds that they are more practical and economical so that they can attract students' interest in reading and can be used as a medium used to improve language skills. Character values can be inserted in the Sigil e-book media.